Analisis Kelayakan Investasi Workshop Inglorious Cloth Ditinjau Dari Aspek Pasar, Aspek Teknik, Dan Aspek Finansial Dikota Bandung - Zaky Abdul Karim; Budi Praptono; Aulia Fashanah (eProceedings of Engineering, 2015)
Abstract - Bandung has been known as the center of the fashion industry in Indonesia, especially to young people and tourists. Bandung the number density of population of 2,483,977 inhabitants, as a choice tourist city, seen the number of tourists increased from year to year, while age in 18-26 for 1.083.615 inhabitants. With the increasing population, the number of tourist arrivals, and the number of students in the city of Bandung, in other words, PDRB per capita Bandung automatically increased, with the opportunity to see it like that, then Inglorious Cloth want to set up a workshop in downtown Bandung, namely Tamim area Pasar Baru Bandung. Before making workshop Inglorious Cloth, conduct a feasibility study whether a workshop will be appropriate to the market aspects, technical aspects and financial aspects. Market size is known by way of distributing questionnaires. For the analysis of the technical aspects of location determination, the determination of the amount of human resources, the determination of production equipment and technical specifications compared with other workshops. For the financial aspects of the investment expenditure and revenue estimates obtained using the results of the analysis calculations have been done before. Period set for the financial projections is 5 years with MARR = 12%. The result of the calculation of the level of investment that is NPV = Rp. 152.424.760, IRR = 35,18% and PBP = 5,017 years. Workshop Inglorious Cloth declared eligible for the value of IRR is greater than the value of MARR and the NPV is positive. Keywords - Feasibility Analysis, NPV, IRR, PBP, Workshop Inglorious Cloth